Relevance of Educational Thoughts of J. Krishnamurti in the Context of Education for Peace - Singh, Parmanand; Singh, Parnita; Yadav, Jayashankar (JOURNAL OF INDIAN EDUCATION, 2010)
In this paper, educational thoughts of J. Krishnamurti were studied in the context of education for peace. It has been found that his thoughts are quite relevant in the reconstruction of our educational system. The philosophy and programme for peace education may be developed on this basis.